Proceedings of the 13th International Scientific Conference : Computer Aided Engineering - Rusiński, Eugeniusz; Pietrusiak, Damian (Springer, 2017)
These proceedings of the 13th International Conference on Computer Aided Engineering present selected papers from the event, which was held in Polanica Zdrój, Poland, from June 22 to 25, 2016. The contributions are organized according to thematic sections on the design and manufacture of machines and technical systems; durability prediction; repairs and retrofitting of power equipment; strength and thermodynamic analyses for power equipment; design and calculation of various types of load-carrying structures; numerical methods for dimensioning materials handling; and long-distance transport equipment. The conference and its proceedings offer a major interdisciplinary forum for researchers and engineers to present the most innovative studies and advances in this dynamic field.
International conference proceedings.
Keywords: Computer-aided engineering -- Congresses.; elektronické knihy; electronic books